A generalized fault location method based on voltage sags for distribution network. (23rd September 2013) - Awalin, Lilik Jamilatul; Mokhlis, Hazlie; Abu Bakar, AbHalim; Mohamad, Hasmaini; Illias, Hazlee A.
Abstract: An enhanced fault location method based on voltage sag profiles for distribution networks is presented in this paper. In other previous methods, only a single measurement has been used. The proposed method can be used with any number of measurements in the network, making it more general. A new ranking approach that addresses multiple possibilities of the faulted section is proposed. Different case studies with various numbers of measurements are performed on a large 11‐kV network with the main feeder consisting of 42 buses to validate the method. The test results show that there is an improvement in terms of accuracy in detecting the faulted section in the first attempt for each additional measurement. Therefore, by utilizing the average value of each measurement, a better accuracy of fault location can be achieved. © 2013 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.